The Impact of Working Capital Efficiency, Cash Conversion Cycle, and Current Ratio on Profitability with Firm Size as a Moderating Variable - Yohanes Prammoedya Octavianus; Achmad Badjuri (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine the influence of Working Capital Efficiency, Cash Conversion Cycle, and Current Ratio on Profitability with Firm Size as a moderation variable in manufacturing companies listed on the Indonesia Stock Exchange for the 2021–2024 period. This study uses a quantitative approach with secondary data in the form of annual financial statements. The research sample was obtained through the purposive sampling method resulting in 140 observations. Data analysis was carried out using panel data regression and Moderated Regression Analysis (MRA) with the help of EViews 13 software. The results of the model test show that the Fixed Effect Model is the most accurate estimation model. Partially, the results showed that the Cash Conversion Cycle had a negative and significant effect on profitability, while the Current Ratio had a positive and significant effect on profitability. Meanwhile, Working Capital Efficiency has no significant effect on profitability. The results of the moderation test showed that Firm Size was not able to moderate the relationship between Working Capital Efficiency, Cash Conversion Cycle, and Current Ratio to Profitability. Simultaneously, all research variables had a significant effect on profitability. These findings confirm the importance of cash cycle and liquidity management in improving the financial performance of manufacturing companies.